Analysis of ERP Critical Failure Factors: A Case Study in an Indonesian Mining Company - Shinta Dewi Larasati; Imairi Eitiveni; Pramudya Mahardhika (Jurnal Sistem Informasi, 2023)
ERP is a useful application for companies to run day-to-day operations by automating business processes, but the complexity and difficulty of deploying ERP systems causes unanticipated implementation failures. Around 70% of ERP implementation fails to produce expected benefits, and three quarters of these projects fail. This study aims to uncover potential reasons that cause the failure of ERP system adoption using Company XYZ, a mining company as the case. A questionnaire was distributed to its management and employees. TOPSIS approach was used to rank the variables according to their significance in affecting failure of ERP systems implementation. The findings revealed that the two most important critical failure causes for ERP implementation are bad understanding of organization’s business processes and poor business process reengineering. The company needs to conduct a deeper analysis of the existing business processes in the business unit to be able to determine more appropriate business process reengineering for ERP implementation in the future. Companies and academics can utilize the study's findings as a helpful resource to identify the cause of ERP implementations failure